2022
DOI: 10.1038/s41598-022-14915-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of traditional and DNA metabarcoding samples for monitoring tropical soil arthropods (Formicidae, Collembola and Isoptera)

Abstract: The soil fauna of the tropics remains one of the least known components of the biosphere. Long-term monitoring of this fauna is hampered by the lack of taxonomic expertise and funding. These obstacles may potentially be lifted with DNA metabarcoding. To validate this approach, we studied the ants, springtails and termites of 100 paired soil samples from Barro Colorado Island, Panama. The fauna was extracted with Berlese-Tullgren funnels and then either sorted with traditional taxonomy and known, individual DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Regional and global metabarcoding‐based studies are currently widely applied. Metabarcoding of pollen loads from pollinators has allowed us to identify the plant species they visit (Bell et al., 2017; Tommasi et al., 2021), as well as to identify terrestrial arthropods from bulk soil samples (Basset et al., 2022; Clarke et al., 2021; Kirse et al., 2021). Further, some applications yield trophic information (Šigut et al., 2017; Toju & Baba, 2018), reveal migratory patterns (Suchan et al., 2019), and even facilitate arthropod monitoring in different tree species based on DNA from rainwater percolating from them (Macher et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Regional and global metabarcoding‐based studies are currently widely applied. Metabarcoding of pollen loads from pollinators has allowed us to identify the plant species they visit (Bell et al., 2017; Tommasi et al., 2021), as well as to identify terrestrial arthropods from bulk soil samples (Basset et al., 2022; Clarke et al., 2021; Kirse et al., 2021). Further, some applications yield trophic information (Šigut et al., 2017; Toju & Baba, 2018), reveal migratory patterns (Suchan et al., 2019), and even facilitate arthropod monitoring in different tree species based on DNA from rainwater percolating from them (Macher et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our understanding of how well metabarcoding represents the composition of flying insect communities compared with conventional morphological methods is still incomplete. Several studies have shown that metabarcoding can perform similarly to morphological approaches (Elbrecht, Vamos, et al, 2017; Herrera‐Mesías et al, 2022; Liu et al, 2020), but the majority of studies come from aquatic ecosystems (Buchner, Macher, et al, 2021; Elbrecht & Leese, 2015; Groendahl et al, 2017; Mora et al, 2019; Steyaert et al, 2020; Zimmermann et al, 2015) or terrestrial soil fauna (Basset et al, 2022; Oliverio et al, 2018). Moreover, most studies only investigate a small subset of defined target species or higher taxonomic levels (e.g., family level or genus level), necessitating examinations of how well metabarcoding performs across the entire community at species level.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most studies only investigate a small subset of defined target species or higher taxonomic levels (e.g., family level or genus level), necessitating examinations of how well metabarcoding performs across the entire community at species level. Furthermore, some studies do not compare identification methods using the same sample and specimens (e.g., Basset et al, 2022; Lobo et al, 2017; Mora et al, 2019; Schenk et al, 2020). Doing so can help to determine whether the same specimens identified by one method are also identified by the other.…”
Section: Introductionmentioning
confidence: 99%
“…2009, Von Cräutlein et al 2011, Antil et al 2023, Chac and Thinh 2023). Advances in high-throughput sequencing over this interval have enabled new approaches (eDNA, metabarcoding) which infer the species that contributed to DNA extracts prepared from environmental samples or bulk collections of specimens (Valentini et al 2016, Hallam et al 2021, Basset et al 2022, Cote et al 2023). However, these workflows require access to a reference library of barcode sequences constructed through the analysis of single specimens.…”
Section: Introductionmentioning
confidence: 99%